Graham Dominy, Last Outpost on the Zulu Frontiers – Fort Napier and the British Imperial Garrison (Historia, 2021)
In the Foreword to Andrew Duminy and Bill Guest’s Natal and Zululand: From EarliestTimes to 1910, published in 1989, the late Professor Colin Webb remarked, withapprobation, that exploration of Natal’s past continued vigorously. Graham Dominy’sthorough account of the role of the garrison at Fort Napier exemplifies andembellishes that practice. At the outset he makes a significant observation about thestrength of the garrison which has great relevance to the frugal way the Britishmaintained their empire: “The power of the garrison was less than it sought toportray, but it was a token of the greater power of the empire, which could bebrought into play if locally challenged” (p xvi). As such, the garrison symbolisedBritish hegemony and promoted a sense of security amongst the small settlerpopulation. But as Dominy also notes, “the garrison masked the weaknesses of thestate through military pageantry and marched out on minor expeditions in responseto panic and rumours of invasion” (p 58). Although he does not make this point, theextent to which settlers were consistently aware of their vulnerability was theirinvolvement in the rifle associations. No other civic organisation was as prolific.Initiated by Ordinance 11 of 1855, by 1904 there were 62 Volunteer Corps or rifleassociations, as they were then called.1